Ternary platinum-based ordered alloy catalyst, preparation method thereof and fuel cell
By combining ball milling and high-temperature calcination methods, organic small molecule ligands are added to prepare a ternary platinum-based ordered alloy catalyst, which solves the problems of complex preparation and environmental unfriendliness in the existing technology, and realizes a catalyst with controllable particle size and high ORR performance, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202510882027.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-09-23
AI Technical Summary
The preparation process of existing platinum-based alloy catalysts is complex and environmentally unfriendly, making it difficult to achieve efficient mass production of high-ORR performance catalysts with controllable particle size.
The ball milling method is combined with the high-temperature calcination method, and an organic small molecule ligand is added during the ball milling mixing stage to form a coordination bond, so that the doping elements N and/or S enter the alloy particle phase, preventing agglomeration, and preparing a ternary platinum-based ordered alloy catalyst.
A catalyst with smaller particle size and higher performance was obtained, which is environmentally friendly and suitable for large-scale production. Its ORR activity and stability are better than those of commercial catalysts, meeting the DOE2025 goals.
Smart Images

Figure CN120690876A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of platinum alloy catalysts, and in particular to a ternary platinum-based ordered alloy catalyst, a preparation method thereof, and a fuel cell. Background Art
[0002] Platinum-based catalysts have become the catalyst of choice for proton exchange membrane fuel cells (PEMFCs) due to their promising oxygen reduction reaction performance. However, in practical applications, they face problems such as excessive dosage and high cost. To address these issues, the most effective approach in the past decade has been to alloy Pt with some transition metals. The resulting PtM alloys can reduce Pt dosage while significantly improving the catalytic activity of the oxygen reduction reaction at the fuel cell cathode. Based on this, the development of platinum alloy electrocatalysts is imminent.
[0003] However, the synthesis processes of most PtM alloys are relatively complicated, which limits their large-scale production. At the same time, the preparation process basically requires the participation of organic solvents, which will produce organic waste liquid and damage the environment. Known CN116422342A discloses a solvent thermal reduction method for preparing platinum-based alloy catalysts. This method is the mainstream synthesis method of platinum-based alloy catalysts. Different platinum-based alloy catalysts can be prepared by high-temperature calcination of the solid obtained after mixing and heating different metal salts, carriers and reducing solutions. This method has high universality, but the process is complicated and the organic solvents used are harmful to the environment. Therefore, the preparation method of PtM alloys needs to be optimized under the premise of ensuring high performance of the catalyst, and the ball milling method has emerged. Among them, CN111224116A discloses a method for preparing a metal-containing nitrogen-hybridized carbon-based catalytic material. This method can directly mix and ball-mill to prepare a catalyst precursor after preliminary heat treatment of raw materials such as carbon source, nitrogen source, structure-directing agent, and metal precursor, and then pyrolyze under inert gas or reducing atmosphere to obtain the catalyst. This method does not require the use of organic solvents, is more environmentally friendly, and is easy to synthesize catalysts in batches. However, directly adding raw materials during ball milling can easily cause the catalyst to agglomerate, resulting in a loss of active sites and poor performance.
[0004] Therefore, how to effectively utilize the ball milling method to efficiently and batch-produce platinum-based alloy catalysts with controllable particle size and high ORR performance without the involvement of solvents is a technical problem that needs to be solved urgently. Summary of the Invention
[0005] To address the above-mentioned technical problems, the present invention provides a ternary platinum-based ordered alloy catalyst, a preparation method thereof, and a fuel cell. The present invention combines ball milling with high-temperature calcination, and adds an organic small molecule ligand during the ball milling mixing stage to participate in the reaction and prepare the catalyst. The organic small molecule ligand can form coordination bonds with the Pt particles and transition metal particles, allowing the S element and / or N element in the organic small molecule ligand to be doped into the bulk phase of the alloy particles. The addition of the doping element can also effectively prevent the catalyst from agglomerating due to ball milling, thereby obtaining a catalyst with a smaller alloy nanoparticle size, thereby improving catalyst performance. The preparation process does not require the use of solvents, especially organic solvents, and does not generate organic waste liquid, making it environmentally friendly. Furthermore, the preparation method is extremely simple and safe, making it suitable for large-scale production.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a ternary platinum-based ordered alloy catalyst, the preparation method comprising the following steps:
[0008] The organic small molecule ligand, Pt precursor, M1 precursor, M2 precursor and carbon support are uniformly mixed by ball milling to obtain a catalyst precursor, which is then calcined to obtain a ternary platinum-based ordered alloy catalyst;
[0009] The organic small molecule ligand includes a doping element, and the doping element includes N element and / or S element;
[0010] In the M1 precursor and the M2 precursor, M1 and M2 are each independently a transition metal element.
[0011] It should be noted that the “small organic molecule ligand” mentioned in the present invention refers to an organic ligand with a molecular weight of less than or equal to 500.
[0012] The present invention ball-mills an organic small molecule ligand with a Pt precursor, an M1 precursor, an M2 precursor, and a carbon carrier. During the ball milling process, local high temperature and high pressure generated by high-energy collisions can promote the reaction so that the N-containing and / or S-containing groups in the organic small molecule ligand can form strong coordination bonds with the Pt particles and the transition metal particles, so that the S element and / or N element in the organic small molecule ligand is doped into the bulk phase of the alloy particles. At the same time, the addition of the doping elements can also effectively prevent the catalyst from agglomerating due to ball milling, thereby obtaining a catalyst with a smaller alloy nanoparticle size and improving the catalyst performance. In addition, no solvent is required in the preparation process, especially the use of organic solvents is avoided, no organic waste liquid is generated, and the process is environmentally friendly. At the same time, the process is extremely simple and safe, and is suitable for large-scale production.
[0013] In addition, the ball milling mixing adopted in the present invention has more preparation advantages than other mixing processes, such as impregnation mixing. Ball milling mainly produces strong shearing, extrusion and collision effects on each catalyst component through the high-speed impact and rolling of the grinding medium, which can force the mixing of micron-level or even nano-level catalyst components, overcome the agglomeration and electrostatic effects between particles, and thus achieve uniform dispersion at the atomic or nano-level. The impregnation method relies entirely on the diffusion of the solvent. Each catalyst component must first be dissolved in the solvent and then adsorbed into the carrier pores through diffusion, which may lead to uneven local loading concentration. Moreover, the impregnation method is mainly based on physical adsorption. The active components are adsorbed on the carrier surface through van der Waals forces or chemical bonds. The bond energy is weak, and the active components are prone to agglomeration, which in turn affects the performance of the catalyst.
[0014] As a preferred technical solution of the present invention, the organic small molecule ligand includes any one or a combination of at least two of hexanethioamide, pentanethioamide, dithiothreitol, 1-thioglycerol, pyroglutamic acid, sodium pyroglutamate, histidine, valine, aspartic acid, sodium aspartate, serine, citrulline, glycine, sodium glycinate, glutamic acid, sodium glutamate, sodium thioacetate, thiolactic acid, cysteine, threonine, and theanine, preferably any one or a combination of at least two of glycine, sodium glycinate, sodium glutamate, sodium thioacetate or thiolactic acid.
[0015] The organic small molecule ligand used in the present invention is non-toxic and harmless, does not produce any harmful products when used in the entire reaction system, and is environmentally friendly. The structural formula of the organic small molecule ligand used in the present invention includes any one or a combination of at least two of a carboxylic acid functional group, a carboxylate functional group, a carbonyl functional group or a hydroxyl functional group. The above functional groups can form a strong coordination bond with the Pt particles and the transition metal particles, especially the carboxylic acid functional group or the carboxylate functional group, which can effectively avoid the agglomeration of the material during the ball milling process. The alloy particles are highly dispersed on the carrier, laying the necessary foundation for the high ORR activity of the catalyst.
[0016] As a preferred technical solution of the present invention, the Pt precursor includes any one of sodium chloroplatinate, potassium chloroplatinate, sodium chloroplatinite, potassium chloroplatinite, platinum tetrachloride or potassium hexaiodideplatinate, or a combination of at least two thereof.
[0017] Preferably, the M1 precursor includes any one of an iron source, a cobalt source, a nickel source, a copper source or a zinc source.
[0018] Preferably, the M2 precursor includes any one of a manganese source, a chromium source, an iron source, a cobalt source, a nickel source, a copper source or a zinc source.
[0019] Preferably, the molar ratio of the organic small molecule ligand to the Pt element in the Pt precursor is 1:(0.1-25), for example, 1:0.1, 1:1, 1:3, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20, 1:22 or 1:25, etc., preferably 1:(0.5-10).
[0020] In the present invention, the molar ratio of the organic small molecule ligand to the Pt element in the Pt precursor is controlled to be 1:(0.5-10), which can control the uniformity and size of the Pt nanoparticles during the calcination process. Excessive organic small molecule ligands can prevent the catalyst from effectively nucleating and reduce particle size uniformity; too little organic small molecule ligands can lead to excessive growth of Pt nanoparticles and increase in particle size, both of which can lead to reduced ORR performance of the catalyst.
[0021] It should be noted that the present invention does not impose any specific requirements or special restrictions on the type of carbon carrier, and any carbon carrier commonly used in the art, such as EC300-JD, EC600-JD, XC-72 or BP2000, can be used.
[0022] As a preferred technical solution of the present invention, the rotation speed of the ball mill is 100 r / min to 600 r / min, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min or 600 r / min.
[0023] Preferably, the ball milling time is 0.3 h to 12 h, for example, 0.3 h, 1 h, 3 h, 5 h, 8 h, 10 h or 12 h.
[0024] Preferably, the ball-to-material ratio of the ball mill is (5-50):1, such as 5:1, 10:1, 20:1, 30:1, 40:1 or 50:1.
[0025] As a preferred technical solution of the present invention, the calcination is carried out under a reducing atmosphere.
[0026] Preferably, the gas used in the reducing atmosphere includes any one of H2, H2 / Ar mixed gas or H2 / N2 mixed gas.
[0027] Preferably, the volume concentration of H2 in the H2 / Ar mixed gas or the H2 / N2 mixed gas is 2% to 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0028] Preferably, the heating rate of the calcination is 1°C / min to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.
[0029] Preferably, the calcination holding temperature is 450°C to 950°C, for example, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C or 950°C.
[0030] Preferably, the calcination holding time is 0.5 h to 10 h, for example, 0.5 h, 2 h, 4 h, 6 h, 8 h or 10 h.
[0031] As a preferred technical solution of the present invention, after the calcination, the process further comprises the steps of acid washing, solid-liquid separation, drying and heat treatment of the obtained calcined product.
[0032] Preferably, the acid solution used for pickling includes any one of perchloric acid, sulfuric acid or acetic acid.
[0033] Preferably, the concentration of the acid solution used for pickling is 0.1 mol / L to 0.5 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L.
[0034] Preferably, the pickling temperature is 30°C to 85°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or 85°C.
[0035] Preferably, the pickling time is 0.5 h to 24 h, for example, 0.5 h, 5 h, 10 h, 15 h, 20 h or 24 h.
[0036] It should be noted that the present invention does not impose specific requirements or special limitations on the solid-liquid separation and drying methods, and common methods in the field are applicable to the present invention. There are no specific requirements or special limitations on the drying temperature and time, as long as the obtained product is completely dried.
[0037] As a preferred technical solution of the present invention, the heat treatment is carried out under a reducing atmosphere.
[0038] Preferably, the gas used in the reducing atmosphere includes any one of H2, H2 / Ar mixed gas or H2 / N2 mixed gas.
[0039] Preferably, the volume concentration of H2 in the H2 / Ar mixed gas or the H2 / N2 mixed gas is 2% to 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0040] Preferably, the heating rate of the heat treatment is 1°C / min to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.
[0041] Preferably, the holding temperature of the heat treatment is 200℃~500℃, for example, 200℃, 220℃, 250℃, 280℃, 300℃, 320℃, 350℃, 380℃, 400℃, 420℃, 450℃, 480℃ or 500℃, etc.
[0042] Preferably, the holding time of the heat treatment is 0.5 h to 10 h, for example, 0.5 h, 2 h, 4 h, 6 h, 8 h or 10 h.
[0043] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0044] The organic small molecule ligand, Pt precursor, M1 precursor, M2 precursor and carbon support are ball milled at 100r / min~600r / min for 0.3h~12h to mix evenly, with a ball-to-material ratio of (5~50):1 to obtain a catalyst precursor, and the mixture is heated to 450℃~950℃ at a rate of 1℃ / min~10℃ / min under a reducing atmosphere and calcined for 0.5h~10h. The obtained calcined product is acid-washed with an acid solution with a concentration of 0.1mol / L~0.5mol / L at 30℃~85℃ for 0.5h~24h, filtered, dried, and heated to 200℃~500℃ at a rate of 1℃ / min~10℃ / min under a reducing atmosphere for 0.5h~10h to obtain a ternary platinum-based ordered alloy catalyst;
[0045] The organic small molecule ligand includes a doping element, and the doping element includes N element and / or S element; in the M1 precursor and the M2 precursor, M1 and M2 are each independently a transition metal element; the molar ratio of the organic small molecule ligand to the Pt element in the Pt precursor is 1:(0.1~25).
[0046] In a second aspect, the present invention also provides a ternary platinum-based ordered alloy catalyst, which includes a carbon support and ternary platinum-based alloy nanoparticles dispersed on the surface of the carbon support, wherein the ternary platinum-based alloy nanoparticles are an intermetallic ordered alloy formed by Pt element, transition metal element M1 and transition metal element M2, and the bulk phase of the ternary platinum-based alloy nanoparticles includes doping elements, and the doping elements include N element and / or S element.
[0047] In the present invention, the doping of N element can regulate the ORR performance of the catalyst, reduce the surface energy of Pt, M1 and M2 atoms on the surface of the nanoparticles, inhibit the dissolution of Pt atoms from the alloy nanoparticles during the ORR reaction, and also play a role in inhibiting agglomeration; the doping of S element can effectively inhibit the agglomeration of Pt nanoparticles and prepare a ternary platinum-based alloy catalyst with a suitable particle size; the combination of transition metal element M2 and transition metal element M1 can further regulate the electronic structure of Pt and optimize the adsorption strength of ORR reaction intermediates. In addition, the doping elements N element and / or S element are doped into the bulk phase of the ternary platinum-based alloy nanoparticles, rather than directly doping N element and / or S element into the carbon support in advance. This doping method can better play the role of the doping elements, inhibit the agglomeration of alloy nanoparticles, improve catalyst performance, and achieve better ORR performance.
[0048] As a preferred technical solution of the present invention, the transition metal element M1 includes any one of Fe, Co, Ni, Cu or Zn.
[0049] Preferably, the transition metal element M2 includes any one of Mn, Cr, Fe, Co, Ni, Cu or Zn.
[0050] Preferably, the average particle size of the ternary platinum-based alloy nanoparticles is 2 nm to 10 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0051] Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst as 100wt%, the mass of the Pt element is 10wt% to 50wt%, for example, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%, etc., preferably 25wt% to 35wt%.
[0052] Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst as 100wt%, the mass of the transition metal element M1 is 3wt% to 30wt%, for example, 3wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%, etc., preferably 6wt% to 10wt%.
[0053] Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst as 100wt%, the mass of the transition metal element M2 is 0.1wt% to 10wt%, for example, 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc., preferably 2wt% to 5wt%.
[0054] Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst as 100wt%, the mass of the doping element is 0.1wt% to 5wt%, for example, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc., preferably 0.5wt% to 2wt%.
[0055] Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst being 100 wt%, excluding the mass of the Pt element, the mass of the transition metal element M1, the mass of the transition metal element M2 and the mass of the doping element, the remainder is the carbon support.
[0056] In a third aspect, the present invention further provides a fuel cell, comprising a ternary platinum-based ordered alloy catalyst prepared by the preparation method described in the first aspect, or a ternary platinum-based ordered alloy catalyst described in the second aspect.
[0057] Compared with the prior art, the present invention has at least the following beneficial effects:
[0058] 1) The ternary platinum-based ordered alloy catalyst provided by the present invention has ternary platinum-based alloy nanoparticles with suitable particle size and high dispersion on the carrier. By relying on the addition of organic small molecule ligands, with the assistance of the nitrogen and / or sulfur elements in the organic small molecule ligands, the agglomeration phenomenon that is easy to occur during conventional ball milling is effectively avoided.
[0059] 2) The ternary platinum-based ordered alloy catalyst provided by the present invention has high electrochemical activity, and its ORR activity is higher than that of commercial Pt / C and commercial binary alloy PtCo / C catalysts. The ORR stability performance of the catalyst is also excellent, both meeting the DOE2025 goals.
[0060] 3) The doping elements N and / or S in the present invention are doped into the bulk phase of the ternary platinum-based alloy nanoparticles, rather than directly doping the N and / or S elements into the carbon support in advance. This doping method can better exert the role of the doping elements, inhibit the agglomeration of the alloy nanoparticles, improve the catalyst performance, and achieve better ORR performance.
[0061] 4) The preparation process of the present invention does not require the use of any solvent, especially avoids the use of organic solvents, does not generate organic waste liquid, is environmentally friendly, and the process is extremely simple and safe, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a TEM image of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention.
[0063] Figure 2 3 is the XRD pattern of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention.
[0064] Figure 3 This is a comparison chart of the activities of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention, the commercial Pt / C catalyst provided in Comparative Example 5, and the PtCo / C catalyst provided in Comparative Example 6.
[0065] Figure 4 These are the ORR forward scanning polarization curves of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention in an O2-saturated 0.1MHClO4 solution at the initial stage and after 30,000 cycles of stability testing.
[0066] Figure 5 1 is the cyclic voltammetry curve of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention after the initial and 30,000 cycles of stability testing. DETAILED DESCRIPTION
[0067] The technical solution of the present invention will be further described below with reference to the accompanying drawings and through specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0068] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0069] Example 1
[0070] This embodiment provides a method for preparing a ternary platinum-based ordered alloy catalyst, the preparation method comprising the following steps:
[0071] 2.12g of platinum acetylacetonate, 0.97g of cobalt acetylacetonate, 0.48g of nickel acetylacetonate, 0.52g of sodium glycinate and 2g of EC600-JD were added to a ball mill, and steel balls were added at a ball-to-material ratio of 35:1. The ball mill was placed in a ball mill and ball-milled at a speed of 400r / min for 3h. The black powder obtained by ball milling was calcined at 900℃ for 2h under H2 / Ar mixed gas (H2 volume concentration is 5%). The calcined product was placed in a 0.1mol / L perchloric acid solution, stirred evenly, and then heated to 80℃ for acid washing for 3h. After the reaction, it was washed with deionized water until neutral and then dried. Finally, it was placed at 400℃ and H2 / Ar mixed gas (H2 volume concentration is 5%) for 1h to obtain an N-PtCoNi / C alloy catalyst.
[0072] Figure 1 The TEM image of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention is shown. As can be seen from the figure, the N-PtCoNi alloy nanoparticles are uniformly dispersed on the carbon support, with an average particle size of 4.4 nm, and the particles are highly dispersed and uniform.
[0073] The N-PtCoNi / C alloy catalyst provided in Example 1 was subjected to X-ray diffraction (XRD) testing. The powder sample was evenly flattened in the groove of the quartz plate and placed in the testing instrument. The instrument tube voltage and tube current were adjusted to 40 kV and 15 mA respectively. The test angle was 10° to 90°, and the scanning speed was 5° min -1 .
[0074] Figure 2 The XRD pattern of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention is shown. As can be seen from the figure, the alloy material is a standard intermetallic ordered alloy and corresponds one-to-one with the standard comparison card.
[0075] Example 2
[0076] This embodiment provides a method for preparing a ternary platinum-based ordered alloy catalyst. The difference between the preparation method and Example 1 is that nickel acetylacetonate is replaced by zinc acetylacetonate to prepare an N-PtCoZn / C alloy catalyst. The remaining preparation methods and parameters are consistent with Example 1.
[0077] Example 3
[0078] This embodiment provides a preparation method of a ternary platinum-based ordered alloy catalyst. The preparation method differs from that of Example 1 in that cobalt acetylacetonate is replaced by iron acetylacetonate, and nickel acetylacetonate is replaced by chromium acetylacetonate to prepare an N-PtFeCr / C alloy catalyst. The remaining preparation methods and parameters are consistent with those of Example 1.
[0079] Example 4
[0080] This embodiment provides a method for preparing a ternary platinum-based ordered alloy catalyst. The difference between the preparation method and Example 1 is that cobalt acetylacetonate is replaced with zinc acetylacetonate to prepare an N-PtZnNi / C alloy catalyst. The remaining preparation methods and parameters are consistent with Example 1.
[0081] Example 5
[0082] This embodiment provides a preparation method of a ternary platinum-based ordered alloy catalyst. The preparation method differs from that of Example 1 in that cobalt acetylacetonate is replaced by zinc acetylacetonate, and nickel acetylacetonate is replaced by manganese acetylacetonate to prepare an N-PtZnMn / C alloy catalyst. The remaining preparation methods and parameters are consistent with those of Example 1.
[0083] Example 6
[0084] This embodiment provides a method for preparing a ternary platinum-based ordered alloy catalyst. The difference between the preparation method and Example 1 is that sodium glycinate is replaced with an equimolar amount of sodium thioacetate to prepare an S-PtCoNi / C alloy catalyst. The remaining preparation methods and parameters are consistent with Example 1.
[0085] Example 7
[0086] This embodiment provides a preparation method for a ternary platinum-based ordered alloy catalyst. The preparation method differs from Example 1 in that the steps of placing the calcined product in a 0.1 mol / L perchloric acid solution, stirring evenly, and then heating to 80°C for acid washing for 3 hours are omitted. After the reaction is completed, the product is washed with deionized water until neutral and then dried. Finally, the product is placed in a 400°C, H2 / Ar mixed gas (H2 volume concentration is 5%) heat treatment condition for 1 hour. After calcining at 900°C for 2 hours, the N-PtCoNi / C alloy catalyst is directly prepared. The remaining preparation methods and parameters are consistent with Example 1.
[0087] Example 8
[0088] This embodiment provides a method for preparing a ternary platinum-based ordered alloy catalyst. The difference between the preparation method and Example 1 is that the molar ratio of sodium glycinate to the Pt element in platinum acetylacetonate is 1:0.1, and the other preparation methods and parameters are consistent with Example 1.
[0089] Example 9
[0090] This embodiment provides a method for preparing a ternary platinum-based ordered alloy catalyst. The difference between the preparation method and Example 1 is that the molar ratio of sodium glycinate to the Pt element in platinum acetylacetonate is 1:25, and the other preparation methods and parameters are consistent with Example 1.
[0091] Comparative Example 1
[0092] This comparative example provides a preparation method of a ternary platinum-based ordered alloy catalyst. The preparation method differs from Example 1 in that the addition of sodium glycinate to the raw materials is omitted, and the remaining preparation methods and parameters remain consistent with Example 1.
[0093] Comparative Example 2
[0094] This comparative example provides a method for preparing a ternary platinum-based ordered alloy catalyst, which adopts an impregnation loading method and comprises the following steps:
[0095] 2.12g of platinum acetylacetonate, 0.97g of cobalt acetylacetonate, 0.48g of nickel acetylacetonate, 0.52g of sodium glycinate, and 2g of EC600-JD were dissolved in a mixture of acetone and water, ultrasonically dispersed, and stirred at room temperature for 6h. The stirred solution was then rotary evaporated to remove the solvent and dried. The resulting black powder was calcined at 900°C for 2h in a H2 / Ar mixed gas (H2 volume concentration of 5%). The calcined product was placed in a 0.1mol / L perchloric acid solution, stirred evenly, and heated to 80°C for 3h for acid washing. After the reaction, it was washed with deionized water until neutral and then dried. Finally, it was heat-treated at 400°C in a H2 / Ar mixed gas (H2 volume concentration of 5%) for 1h to obtain an N-PtCoNi / C alloy catalyst.
[0096] Comparative Example 3
[0097] This comparative example provides a method for preparing a ternary platinum-based ordered alloy catalyst, which comprises the following steps:
[0098] 5g EC600-JD was placed in a tube furnace and heat treated at 800℃ in an ammonia-argon mixed gas atmosphere (NH3 concentration was 5%) for 2h to obtain N-EC600-JD; 2.12g acetylacetonate platinum, 0.97g acetylacetonate cobalt, 0.48g acetylacetonate nickel, and 2.0g N-EC600-JD was added to a ball mill, and steel was added in a ball-to-material ratio of 10:1 and placed in a ball mill. The ball mill was reduced in pressure at 300 r / min for 2 h. The ball-milled material was heated to 900°C at a heating rate of 10°C / min in a H2 / Ar mixed gas atmosphere (the volume concentration of H2 was 5%) and heat treated for 2 h. The resulting powder was placed in a 0.1 mol / L perchloric acid solution, stirred evenly, and then heated to 80°C for acid washing for 3 h. After the reaction was completed, it was washed with deionized water until neutral and then dried. Finally, it was placed at 400°C and heat treated in a H2 / Ar mixed gas (the volume concentration of H2 was 5%) for 1 h to obtain a PtCoNi / NC alloy catalyst.
[0099] Comparative Example 4
[0100] This comparative example provides a method for preparing a binary platinum-based ordered alloy catalyst. The difference between the preparation method and Example 1 is that the addition of nickel acetylacetonate is omitted, and the amount of cobalt acetylacetonate added is changed to 1.45 g to prepare an N-PtCo / C alloy catalyst. The remaining preparation methods and parameters are consistent with Example 1.
[0101] Comparative Example 5
[0102] This comparative example provides a commercial Pt / C catalyst.
[0103] Comparative Example 6
[0104] This comparative example provides a commercial PtCo / C catalyst.
[0105] The average particle size of the alloy nanoparticles and the mass proportion of each component in the catalysts provided in Examples 1 to 9 and Comparative Examples 1 to 4 were tested. The specific test results are shown in Table 1.
[0106] The catalysts of Examples 1 to 9 and Comparative Examples 1 to 4 were subjected to a rotating disk electrode (RDE) test. The specific test method is as follows:
[0107] Take 3mg of catalyst and disperse it in a mixture of 780μL isopropanol and 200μL deionized water, add 20μL 5% Nafion solution, and ultrasonicate for 1h. Then drop 10μL of the dispersed ink on a disk (0.2475cm 2 ) electrode, fully dried under the baking lamp, and made into 40ug Pt cm -2 The electrode head with catalyst loading was used for testing. The specific electrochemical characterization test was carried out in a standard three-electrode system with a carbon rod as the counter electrode and a saturated calomel electrode as the reference electrode. The test was carried out at room temperature. The ORR polarization curve was measured in an O2-saturated 0.1M HClO4 electrolyte, and the background CV curve was measured in an N2-saturated 0.1M HClO4 electrolyte. The specific scanning potential was 0.1-1.1V RHE , the scan rate was 10 mV s -1 The specific test results are shown in Table 1.
[0108] Table 1
[0109]
[0110]
[0111] Figure 3The activity comparison diagram of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention, the commercial Pt / C catalyst provided in Comparative Example 5, and the PtCo / C catalyst provided in Comparative Example 6 is shown. As can be seen from the figure, the mass specific activity of Example 1 is 0.889Amg Pt -1 , respectively, commercial Pt / C catalyst (0.18Amg Pt -1 ) and is 4.9 times that of commercial PtCo / C catalyst (0.45Amg Pt -1 ), indicating that the ORR performance of the N-PtCoNi / C alloy catalyst of the present invention is higher.
[0112] Figure 4 The ORR forward scanning polarization curves of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention are shown in the initial and 30,000 cycles of stability testing in an O2-saturated 0.1MHClO4 solution. Figure 5 The cyclic voltammetry curves of the initial and 30,000 cycle stability tests of the N-PtCoNi / C alloy catalyst provided in Example 1 of the present invention are shown. As can be seen from the figure, the initial ORR half-wave potential of the N-PtCoNi / C alloy catalyst provided in Example 1 is 0.94 V. After 30,000 cycles of attenuation test, the half-wave potential decays by 8.6 mV, the area specific activity (SA) decays by 25.9%, and the mass specific activity (MA) decreases from 0.889 A mg Pt -1 Reduced to 0.67Amg Pt -1 , attenuated by 24.7%. The ECSA of the catalyst remained basically unchanged before and after 30,000 cycles of attenuation test, and the performance met the DOE2025 indicators proposed by the U.S. Department of Energy.
[0113] The test results show that:
[0114] (1) It can be seen from Examples 1 to 9 that the catalyst provided by the present invention exhibits excellent ORR performance, and its performance is due to the effect of the doping elements (N element and / or S element) in the catalyst, which can make the alloy nanoparticles uniformly and fully dispersed on the carbon support; at the same time, the transition metal elements M1 and M2 can produce a synergistic effect with the N element and / or S element, which can reduce the surface energy of the Pt atoms on the surface of the alloy nanoparticles and inhibit the dissolution of the Pt atoms during the ORR reaction; the transition metal can also help the doping elements in the catalyst to strengthen the anchoring effect on the alloy nanoparticles, further inhibiting the agglomeration, migration and Ostwald ripening process of the alloy nanoparticles during the catalytic process, which is beneficial to the improvement of the ORR performance of the catalyst.
[0115] (2) It can be seen from Examples 1 and 8 to 9 that the present invention further regulates the molar ratio of the organic small molecule ligand to the Pt element in the Pt precursor to 1: (0.5 to 10), which can better control the uniformity and size of the Pt nanoparticles during the heat treatment process, and is more conducive to improving the ORR performance of the catalyst.
[0116] (3) It can be seen from Example 1 and Comparative Example 1 that when the addition of the organic small molecule ligand sodium glycinate is omitted, the particle size of the ternary platinum-based alloy nanoparticles is 7.8 nm, and the particles agglomerate to a certain extent. After 30,000 cycles of attenuation test, the mass specific activity decays by 50.1%. Its particle size and activity are not as suitable for actual fuel cell applications as Example 1. This further indicates that the addition of organic small molecule ligands during the ball milling process and the doping of organic small molecule ligands into the bulk phase of the ternary platinum-based alloy nanoparticles play a key role in regulating the catalyst particle size, activity, and stability.
[0117] (4) It can be seen from Example 1 and Comparative Example 2 that the catalyst particle size and electrochemical activity obtained by the two methods are not much different. However, the ball milling method does not require the use of any solvent in the entire preparation process, especially avoids the use of organic solvents, does not generate organic waste liquid, is environmentally friendly, and successfully prepares high-performance catalysts while achieving easy batch production of the preparation method. The impregnation method may cause the active components to agglomerate due to uneven loading concentration, which in turn affects the ORR stability of the catalyst.
[0118] (5) It can be seen from Example 1 and Comparative Example 3 that when the doping element is doped into the carbon support, the catalyst particle size becomes slightly larger and the electrochemical performance decreases slightly, indicating that the doping position of the doping element has an impact on the ORR stability of the catalyst.
[0119] (6) It can be seen from Example 1 and Comparative Example 4 that the combined use of transition metal element M2 and transition metal element M1 can further regulate the electronic structure of Pt and optimize the adsorption strength of ORR reaction intermediates. When one of the transition metal elements is omitted, the ORR stability of the resulting binary platinum-based ordered alloy catalyst is significantly reduced.
[0120] In summary, the present invention combines the ball milling method and the high-temperature calcination method, and adds an organic small molecule ligand to participate in the reaction to prepare a catalyst during the ball milling mixing stage. The organic small molecule ligand can form a coordination bond with the Pt particles and the transition metal particles, so that the S element and / or N element in the organic small molecule ligand is doped into the bulk phase of the alloy particles. At the same time, the addition of the doping element can also effectively prevent the catalyst agglomeration phenomenon caused by ball milling, thereby obtaining a catalyst with a smaller alloy nanoparticle size, thereby improving the catalyst performance. No solvent is required in the preparation process, especially no organic solvent is used, no organic waste liquid is generated, and it is environmentally friendly. At the same time, the preparation method is extremely simple and safe, and is suitable for large-scale production.
[0121] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.
Claims
1. A method for preparing a ternary platinum-based ordered alloy catalyst, characterized in that: The preparation method comprises the following steps: The organic small molecule ligand, Pt precursor, M1 precursor, M2 precursor and carbon support are uniformly mixed by ball milling to obtain a catalyst precursor, which is then calcined to obtain a ternary platinum-based ordered alloy catalyst; The organic small molecule ligand includes a doping element, and the doping element includes N element and / or S element; In the M1 precursor and the M2 precursor, M1 and M2 are each independently a transition metal element.
2. The preparation method according to claim 1, characterized in that The organic small molecule ligand includes any one or a combination of at least two of hexanethioamide, pentanethioamide, dithiothreitol, 1-thioglycerol, pyroglutamic acid, sodium pyroglutamate, histidine, valine, aspartic acid, sodium aspartate, serine, citrulline, glycine, sodium glycinate, glutamic acid, sodium glutamate, sodium thioacetate, thiolactic acid, cysteine, threonine, and theanine, preferably any one or a combination of at least two of glycine, sodium glycinate, sodium glutamate, sodium thioacetate, or thiolactic acid.
3. The preparation method according to claim 1 or 2, characterized in that The Pt precursor includes any one of sodium chloroplatinate, potassium chloroplatinate, sodium chloroplatinite, potassium chloroplatinite, platinum tetrachloride or potassium hexaiodideplatinate, or a combination of at least two thereof; Preferably, the M1 precursor includes any one of an iron source, a cobalt source, a nickel source, a copper source or a zinc source; Preferably, the M2 precursor includes any one of a manganese source, a chromium source, an iron source, a cobalt source, a nickel source, a copper source or a zinc source; Preferably, the molar ratio of the organic small molecule ligand to the Pt element in the Pt precursor is 1:(0.1-25), preferably 1:(0.5-10).
4. The preparation method according to any one of claims 1 to 3, characterized in that The rotation speed of the ball mill is 100 r / min to 600 r / min; Preferably, the ball milling time is 0.3h to 12h; Preferably, the ball-to-material ratio of the ball mill is (5-50):
1.
5. The preparation method according to any one of claims 1 to 4, characterized in that The calcination is carried out under a reducing atmosphere; Preferably, the heating rate of the calcination is 1°C / min to 10°C / min; Preferably, the calcination holding temperature is 450°C to 950°C; Preferably, the calcination holding time is 0.5h to 10h.
6. The preparation method according to any one of claims 1 to 5, characterized in that After the calcination, the steps of acid washing, solid-liquid separation, drying and heat treatment are also included for the calcined product; Preferably, the acid solution used for pickling includes any one of perchloric acid, sulfuric acid or acetic acid; Preferably, the concentration of the acid solution used in the pickling is 0.1 mol / L to 0.5 mol / L; Preferably, the pickling temperature is 30°C to 85°C; Preferably, the pickling time is 0.5h to 24h.
7. The preparation method according to claim 6, characterized in that The heat treatment is carried out under a reducing atmosphere; Preferably, the heating rate of the heat treatment is 1°C / min to 10°C / min; Preferably, the holding temperature of the heat treatment is 200°C to 500°C; Preferably, the heat treatment holding time is 0.5h to 10h.
8. A ternary platinum-based ordered alloy catalyst, characterized in that: The ternary platinum-based ordered alloy catalyst includes a carbon support and ternary platinum-based alloy nanoparticles dispersed on the surface of the carbon support. The ternary platinum-based alloy nanoparticles are an intermetallic ordered alloy formed by Pt element, transition metal element M1 and transition metal element M2. The bulk phase of the ternary platinum-based alloy nanoparticles includes doping elements, and the doping elements include N element and / or S element.
9. The ternary platinum-based ordered alloy catalyst according to claim 8, characterized in that The transition metal element M1 includes any one of Fe, Co, Ni, Cu or Zn; Preferably, the transition metal element M2 includes any one of Mn, Cr, Fe, Co, Ni, Cu or Zn; Preferably, the average particle size of the ternary platinum-based alloy nanoparticles is 2 nm to 10 nm; Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst being 100 wt%, the mass of the Pt element is 10 wt% to 50 wt%, preferably 25 wt% to 35 wt%; Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst being 100 wt%, the mass of the transition metal element M1 is 3 wt% to 30 wt%, preferably 6 wt% to 10 wt%; Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst being 100 wt%, the mass of the transition metal element M2 is 0.1 wt% to 10 wt%, preferably 2 wt% to 5 wt%; Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst being 100 wt%, the mass of the doping element is 0.1 wt% to 5 wt%, preferably 0.5 wt% to 2 wt%; Preferably, based on the total mass of the ternary platinum-based ordered alloy catalyst being 100 wt%, excluding the mass of the Pt element, the mass of the transition metal element M1, the mass of the transition metal element M2 and the mass of the doping element, the remainder is the carbon support.
10. A fuel cell, characterized in that: The fuel cell comprises a ternary platinum-based ordered alloy catalyst prepared by the preparation method according to any one of claims 1 to 7, or a ternary platinum-based ordered alloy catalyst according to claim 8 or 9.
Citation Information
Patent Citations
Multi-atom doped surface platinum-rich catalyst and preparation method thereof
CN116422342A
Preparation method and application of metal-nitrogen doped carbon-based composite material
CN109888318A
Platinum-based alloy catalyst, preparation method thereof and fuel cell
CN118983454A
Platinum-based alloy catalyst, preparation method thereof and fuel cell
CN119315049A
Nitrogen-sulfur double-doped PtM / C catalyst as well as synthesis method and application thereof
CN119400883A
Cited By
Ternary ordered alloy catalyst as well as preparation method and application thereof
CN121172165A